ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR MAHASISWA PENDIDIKAN EKONOMI PADA MATA KULIAH AKUNTANSI KEUANGAN - Herwan, Herwan; Selviani, Ayudho; Nurfadilah, Muhammad Fajri (STKIP Persada Khatulistiwa Sintang, 2025)
The problem in this research is student learning outcomes, which are important indicators of success in higher education which are influenced by various factors. This research aims to identify and analyze factors that influence student learning outcomes. These factors can be divided into two main categories, namely internal and external factors. Internal factors include Interest, Motivation and Readiness in the Learning process. Meanwhile, external factors include family aspects, school aspects and community aspects. Apart from that, the cognitive domain, affective domain and psychomotor domain also play a role in influencing the quality of learning outcomes. This research is a type of qualitative research. The data sources used are primary data sources and secondary data. The data collection techniques used are observation, interviews, documentation, data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions. Based on the results of research conducted by researchers on economic education students at Muhammadiyah University of Bengkulu regarding student learning outcomes in financial accounting courses, it can be concluded that the factors that influence student learning outcomes in financial accounting courses are in terms of interest, motivation and community environment.